DIGITAL MARKETING STRATEGY FOR MSMEs IN THE VUCA ERA (Volatility, Uncertainty, Complexity, and Ambiguity): (Case Study of Snacks MSMEs "The Kriuk") - Lestari, Sri (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Economic growth in Indonesia currently driven by various sectors, one of which is the micro, small and medium enterprise (MSME) sector. However, the biggest problems faced by MSMEs in Indonesia today are capital (51.09%) and marketing (34.72%). In today's VUCA era, business situations are volatile and lead to uncertainty. The emergence of the COVID-19 pandemic is a manifestation of the VUCA situation, so the business world is required to be able to survive in situations that reduce people's social mobility. Therefore, the role of digital marketing is very much needed at this time and is an important part in tackling greater losses for MSMEs. The digital marketing strategies that can be applied by MSME actors include creating a google business account, promoting their product through social media, collaborating with KOL or influencers (endorsement), and email marketing.